Pandangan al-qur'an dan hadis tentang kepercayaan kepada dukun - Hamsahas, Moh Yurdi (Maliki Interdisciplinary Journal, 2025)
This research aims to find out the laws of magic and shamanic rituals by studying the Al-Qur'an, hadith and the opinions of the ulama' in them. There are still many people who fall into this ritual with the aim of wanting to make it easier for every problem they experience. The results of this research show that it is clearly stated in the Al-Qur'an and hadith that the laws of magic and shamanism are haram according to the study of the meaning and opinions of the ulama. The Al-Qur'an has emphasized that a human being cannot know supernatural things. Rasulullah Shalallahu 'Alaihi wa Sallam also spoke in the hadith about the threats of shamanic rituals, namely forms of shirk and forms of disbelief towards Allah Azza wa Jalla. Islam does not allow Muslims to go to and believe in a shaman even if what the shaman says is something that really happened, because the Prophet has warned us as believers not to believe what the shaman says.